DOES MOOSE BROWSING THREATEN EUROPEAN ASPEN REGENERATION IN KOLI NATIONAL PARK, FINLAND? - Härkönen, Sauli; Eerikäinen, Kalle; Lähteenmäki, Riikka; Heikkilä, Risto (Lakehead University, 2008)
Large European aspen (Populus tremula) trees host hundreds of species of which many are threatened species of conifer-dominated, old-growth boreal forests. Aspen is also one of the deciduous tree species most intensively used by moose (Alces alces) in Finland. In conservation areas aspen regeneration is facilitated by large-scale disturbances, especially fires and windstorms, and also by mortality of individual trees and small-scale disturbances that create small openings. These aggregated patches of young aspens provide high quality feeding sites for moose. In Finland, it has been hypothesized that intense browsing pressure by moose on aspen may prevent new aspen cohorts from emerging, and thus endanger the spatio-temporal continuum of aspen occurrence in the long term. The aim of this study was to analyze the influence of moose browsing on the regeneration of aspen in Koli National Park in eastern Finland at 2 different spatial scales, the landscape level and stand level. Our results indicated that moose browsing on aspen has been very intense in the area. At the landscape level, moose damaged (twig-browsing, stem breakage, or bark stripping) 96% of aspens in the southern area and 62% in the northern area of the Park. In addition, 23% of the damaged aspens (all <5 m) were dead in the southern area. According to counts of fecal pellet groups, moose activity was higher in the southern area than the northern area. At the stand level, on average, 79% of the aspens in the southern area and 73% in the northern area were damaged. The proportion of dead aspens (35%) was highest in stands in height category of 5-15 m. Aspen density declined from young to old stands in both areas. Bark stripping was relatively common in the height category of 5-15 m over the whole area. We concluded that the current browsing pressure retards the height development of young aspens because of the repeated break-off of main stems and leader shoots. Although occurrence of aspen may decline due to high browsing pressure by moose, the ...